An Analysis of Transverse Momentum Spectra of Various Jets Produced in High Energy Collisions - Yang-Ming Tai; Pei-Pin Yang; Fu-Hu Liu (Advances in High Energy Physics)
With the framework of the multisource thermal model, we analyze the experimental transverse momentum spectra of various jets produced in different collisions at high energies. Two energy sources, a projectile participant quark and a target participant quark, are considered. Each energy source (each participant quark) is assumed to contribute to the transverse momentum distribution to be the TP-like function, i.e., a revised Tsallis–Pareto-type function. The contribution of the two participant quarks to the transverse momentum distribution is then the convolution of two TP-like functions. The model distribution can be used to fit the experimental spectra measured by different collaborations. The related parameters such as the entropy index-related, effective temperature, and revised index are then obtained. The trends of these parameters are useful to understand the characteristic of high energy collisions.